COVID-19 pandemic impairs medical care of vasculitis patients in Germany: Results of a national patient survey - Kernder, Anna; Filla, Tim; de Groot, Kirsten; Hellmich, Bernhard; Holle, Julia; Lamprecht, Peter; Moosig, Frank; Ruffer, Nikolas; Specker, Christof; Vordenbäumen, Stefan; Schneider, Matthias; Chehab, Gamal (Frontiers in Medicine, 2023)
Objective To analyze the impact of the COVID-19 pandemic on medical care and vaccination acceptance of vasculitis patients in Germany. Methods A web-based national survey was developed by rheumatology centers and vasculitis patient advocacy groups. The survey was distributed nationwide by mail and flyers and could be accessed via a QR-code or weblink from December 2021 to April 2022. Descriptive statistics [mean, median, standard derivation (SD), 25%, 75% quantile] were calculated. 95% confidence intervals were presented for responses that were directly related to the impact of COVID-19 on parameters associated with vasculitis patient care. Results The online survey was completed by 117 patients with small and large vessel vasculitis [granulomatosis with polyangiitis (n = 69), eosinophilic granulomatosis with polyangiitis (n = 16), microscopic polyangiitis (n = 12), giant cell arteritis (n = 17) and Takayasu's arteritis (n = 3)]. Prescheduled rheumatological appointments had been canceled due to the COVID-19 pandemic in 12.6% of the respondents [95% confidence interval (CI), 7.3–20.0%); in 9% (95% CI, 4.5–15.6%)] appointments had been replaced by digital services. Therapeutic regimens were changed (shifted, reduced, or discontinued) due to the pandemic in 15.5% (95% CI 9.5–22.2%). Vaccination coverages were generally high compared to patients with other rheumatic diseases and the general population. Highest vaccination coverage was observed against COVID-19 (98.1% 95% CI 93.9–99.6%). Conclusion Vasculitis patients experienced changes in medical care during COVID-19 pandemic such as cancelation of prescheduled rheumatology appointments and modifications in therapeutic regimens. The overall acceptance rate for vaccination was comparatively high, particularly for vaccination against COVID-19.